Direct Negation in Enrekang People Culture - Sudirman, Sudirman (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The research aims at identifying the sociological factors that influence politeness, and the types of polite negation in Enrekang culture. This qualitative ethnographic research was conducted in Lewaja Sub-District of Enrekang regency. The population consists of 600 adult people of the four villages. The data were collected through questionnaire, observation, recording/video, and interview, and then analysed by applying Brown and Levinson’s theory through socio-pragmatic approach. The result reveal that mostly, Enrekang culture uses Bald on record strategies to indicate polite negation such as: danggimo, daumo, manakanamo, tannia,budamo, and jo o’no’ to all social level, whereas teaq is an impolite response in Enrekang culture. The research also revealed that ages and position are the dominan factors that influence the Enrekang politeness strategies.